2019
DOI: 10.3389/fimmu.2019.01065
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Phenotype of Intrahepatic Sulfatide-Reactive Type II NKT Cells in Humans With Autoimmune Hepatitis

Abstract: Background: Natural Killer T (NKT) cells are CD1d-restricted innate-like T cells that can rapidly release stored cytokines upon recognition of lipid antigens. In mice, type I NKT cells seem to promote liver inflammation, whereas type II NKT cells seem to restrict hepatitis. Here, we aimed at characterizing the role of human type I and type II NKT in patients with autoimmune hepatitis (AIH). Methods: NKT cells were analyzed by flow cytometry in peripheral blood and liver of AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
1
10
0
1
Order By: Relevance
“…Kanter et al also reported the increase in disease severity as the mice were immunized with sulfatide and myelin membrane proteins. A further role of sulfatide as a pro-inflammatory molecule in pathogenesis was discovered in autoimmune hepatitis (59). In contrast, the anti-inflammatory roles of sulfatide were also revealed in autoimmune neuritis and asthma, mediated by sulfatide-activated type II NKT cells (37,60).…”
Section: Discussionmentioning
confidence: 99%
“…Kanter et al also reported the increase in disease severity as the mice were immunized with sulfatide and myelin membrane proteins. A further role of sulfatide as a pro-inflammatory molecule in pathogenesis was discovered in autoimmune hepatitis (59). In contrast, the anti-inflammatory roles of sulfatide were also revealed in autoimmune neuritis and asthma, mediated by sulfatide-activated type II NKT cells (37,60).…”
Section: Discussionmentioning
confidence: 99%
“…168 In patients with AIH, the frequency of MAIT cells and γδ T cells in the blood and liver did not differ significantly. 167 However, other studies demonstrated that MAIT cells were significantly reduced in the peripheral blood and livers of patients with AILD, including PSC, PBC, and AIH, regardless of disease subtype. In diseased livers, MAIT cells accumulated in infiltrates surrounding portal tracts and fibrotic septae, whereas in normal livers, MAIT cells were present in the parenchyma and around portal tracts.…”
Section: Viral Infectionmentioning
confidence: 95%
“…Moreover, intrahepatic non-iNKT cells generated increased TNF-α, decreased IFN-γ and a complete lack of IL-4, indicating the involvement of non-iNKT cells with proinflammatory cytokines in patients with AIH. 167 In contrast, in children with AIH, iNKT cells were increased in the liver but reduced in the peripheral blood, which was localized in the lobular area and portal spaces. 168 In patients with AIH, the frequency of MAIT cells and γδ T cells in the blood and liver did not differ significantly.…”
Section: Viral Infectionmentioning
confidence: 95%
“…Data on the role of innate immunity in AIH are scanty. Natural killer cells type II, which are innate-like T cells recognizing lipid antigens, have been found to produce proinflammatory cytokines in AIH patients, in contrast to healthy controls [ 101 ]. A harming role for macrophages is suggested by the observation of increased expression of VAV1, a protein playing a role in T- and B-cell development and activation, by liver Kupffer cells in AIH patients, as well as by higher serum levels of CD163, produced by activated macrophages, which normalize during disease remission [ 102 , 103 ].…”
Section: Introductionmentioning
confidence: 99%